Pengaruh Kualitas Audit, dan Opinion Shopping Terhadap Penerimaan Opini Audit Going Concern (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017-2020) - Safitri, Anisa Eka; Rina Asmeri; Meri yani (Fakultas Ekonomi, Universitas Ekasakti, 2024)
This study aims to examine the effect of audit quality and opinion shopping on acceptance of going concern audit opinions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The research sample consisted of 15 companies. The method used was purposive sampling, the number of observations was 193 manufacturing companies listed on the IDX for the 2017-2020 period. Annual report data obtained by indo-exchange file(IDX). In this research, the analytical method used is logistic statistics with SPSS Version 21 for windows software. The results of this study indicate that audit quality and opinion shopping have no partial effect on acceptance of going-concern audit opinions. The results of the omnibus test (f test) show that audit quality and opinion shopping simultaneously influence acceptance of going-concern audit opinions.